DETERMINATION OF THE OPTIMAL SEEDING TIMELINES OF WHITE CABBAGE VARIETIES AND HYBRIDS IN THE WEAKLY SALINE SOIL AND CLIMATE CONDITIONS OF KARAKALPAKSTAN - Sayimbetov Alisher; Zhadigerova Mirzagul Sarsenbayevna; Kutlimuratova Dilfuza Baltabaevna; Reyimbaeva Akmaral Azat qizi; Shnibaev Tursinbay Sultanovich (Web of Journals Publishing, 2025)
In 2022-2023, in the slightly saline soil and climatic conditions of Karakalpakstan, the early variety of cabbage Novruz, the hybrid Magnus F1 and the mid-early variety Tashkentskaya 10, hybrids Fresco F1 (20.03; 30.03; 10.04; 20.04; 30.04.) were planted at different times and studied growth and development and impact on yield. The yield of the early ripening variety Navruz in the variant with planting on April 10 (56.2 ha/t) is higher by 4.8-15.0% compared to all variants; the hybrid Magnus F1 in the variant with planting on March 30 (57.5 ha /t) compared to all options was relatively high up to 11.2-48.4%. In the mid-ripening variety Tashkentskaya 10 (04/20), the yield obtained on the control variant is 11.8-34.4% higher than all variants, and in the hybrid Fresco F1 the maximum yield is 65.7 ha/t in the variant planted on April 20 th compared to other options above 3.8-48.0%.